Pro-Coagulant and Pro-Thrombotic Effects of Paclitaxel Mediated by Red Blood Cells - Kim, Keunyoung; Chang, Youn-Kyeong; Bian, Yiying; Bae, Ok-Nam; Lim, Kyung-Min; Chung, Jin-Ho (Thrombosis and Haemostasis, 2018)
Background Paclitaxel is one of the most widely used anti-cancer drugs, but numerous case reports of thrombotic events in the cancer patients using paclitaxel raise concern over its pro-thrombotic risk.Materials and Methods We investigated whether paclitaxel can elicit pro-thrombotic properties in red blood cells (RBCs) through phosphatidylserine (PS) exposure and microvesicle (MV) release.Results In freshly isolated human RBCs, paclitaxel induced thrombin generation through PS exposure and MV release, whereas either coagulation factors or platelets were unaffected. Paclitaxel-induced PS exposure in RBC was mediated by scramblase activation which was induced by calcium-independent protein kinase C (PKC)ζ activation. Paclitaxel also increased RBC-endothelial cell adhesion and RBC aggregate formation which can also contribute to thrombosis. Indeed, intravenous administration of paclitaxel to rats induced PS exposure and PKCζ activation in RBCs in vivo which ultimately promoted venous thrombus formation.Conclusion These results demonstrated that paclitaxel may elicit pro-thrombotic properties in RBCs through PS exposure and MV release, which can ultimately promote thrombus formation.
Keywords: paclitaxel; anti-cancer drug; thrombosis; red blood cells; phosphatidylserine exposure; microvesicle release